A paediatric telecardiology service for district hospitals in south-east England: an observational study. Issue 4 (11th September 2008) - Dowie, R; Mistry, H; Rigby, M; Young, T A; Weatherburn, G; Rowlinson, G; Franklin, R C G
Abstract : Objectives: To compare caseloads of new patients assessed by paediatric cardiologists face-to-face or during teleconferences, and assess NHS costs for the alternative referral arrangements. Design: Prospective cohort study over 15 months. Setting: Four district hospitals in south-east England and a London paediatric cardiology centre. Patients: Babies and children. Intervention: A telecardiology service introduced alongside outreach clinics. Measurements: Clinical outcomes and mean NHS costs per patient. Results: 266 new patients were studied: 75 had teleconsultations (19 of 42 newborns and 56 of 224 infants and children). Teleconsultation patients generally were younger (49% being under 1 year compared with 32% seen personally (p = 0.025)) and their symptoms were not as severe. A cardiac intervention was undertaken immediately or planned for five telemedicine patients (7%) and 30 conventional patients (16%). However, similar proportions of patients were discharged after being assessed (32% telemedicine and 39% conventional). During scheduled teleconferences the mean duration of time per patient in sessions involving real-time echocardiography was 14.4 min, and 8.5 min in sessions where pre-recorded videos were transmitted. Mean cost comparisons for telemedicine and face-to-face patients over 14-day and 6-month follow-up showed the telecardiology service to be cost neutral for the three hospitals with infrequently-held outreach clinics (£1519 vs £1724 respectively after 14 days). Conclusion: Paediatric cardiology centres with small cadres of specialists are under pressure to cope with ever-expanding caseloads of new patients with suspected anomalies. Innovative use of telecardiology alongside conventional outreach services should suitably, and economically, enhance access to these specialists.